Pola dan Kendala Program Diet Gizi Anak ADHD Pada Kesehatan ABK Di TK Cempaka Desa Tanjungsepreh Kab. Magetan - Darmo, Santi Yudhawati (Cipta Media Harmoni, 2025)
Dietary patterns in children with ADHD must be selective because parents play an important role in their success. Therefore, children's growth and development depend on the consistency and dedication of parents. The purpose of this study was to determine the patterns and obstacles of the ADHD children's nutritional diet program carried out by parents so that this study can be a source of reference for parents and teachers of ADHD children who are undergoing a diet program. This study used qualitative techniques with interview methods. The findings of this study explain that the role of parents is very crucial in helping children understand the need to go on a diet and the efforts needed so that ADHD children consume food with ideal nutrition according to their needs regardless of the difficulties and failures experienced by parents. Parenting patterns at home in the success of the ADHD children's diet program are the main ones.